A human MYBPC3 mutation appearing about 10 centuries ago results in a hypertrophic cardiomyopathy with delayed onset, moderate evolution but with a risk of sudden death - Teirlinck Carolien H; Senni Faïza; Malti Rajae El; Majoor-Krakauer Danielle; Fellmann Florence; Millat Gilles; André-Fouët Xavier; Pernot François; Stumpf Michaël; Boutarin Jean; Bouvagnet Patrice (BMC, 2012)
Abstract Background Hypertrophic Cardiomyopathy (HCM) is a genetically heterogeneous disease. One specific mutation in the MYBPC3 gene is highly prevalent in center east of France giving an opportunity to define the clinical profile of this specific mutation. Methods HCM probands were screened for mutation in the MYH7, MYBPC3, TNNT2 and TNNI3 genes. Carriers of the MYBPC3 IVS20-2A>G mutation were genotyped with 8 microsatellites flanking this gene. The age of this MYBPC3 mutation was inferred with the software ESTIAGE. The age at first symptom, diagnosis, first complication, first severe complication and the rate of sudden death were compared between carriers of the IVS20-2 mutation (group A) and carriers of all other mutations (group B) using time to event curves and log rank test. Results Out of 107 HCM probands, 45 had a single heterozygous mutation in one of the 4 tested sarcomeric genes including 9 patients with the MYBPC3 IVS20-2A>G mutation. The IVS20-2 mutation in these 9 patients and their 25 mutation carrier relatives was embedded in a common haplotype defined after genotyping 4 polymorphic markers on each side of the MYBPC3 gene. This result supports the hypothesis of a common ancestor. Furthermore, we evaluated that the mutation occurred about 47 generations ago, approximately at the 10th century. We then compared the clinical profile of the IVS20-2 mutation carriers (group A) and the carriers of all other mutations (group B). Age at onset of symptoms was similar in the 34 group A cases and the 73 group B cases but group A cases were diagnosed on average 15 years later (log rank test p = 0.022). Age of first complication and first severe complication was delayed in group A vs group B cases but the prevalence of sudden death and age at death was similar in both groups. Conclusion A founder mutation arising at about the 10th century in the MYBPC3 gene accounts for 8.4% of all HCM in center east France and results in a cardiomyopathy starting late and evolving slowly but with an apparent risk of sudden death similar to other sarcomeric mutations.